Assessment of Knowledge Regarding Congenital Hypothyroidism Among Doctors in Dhaka City - Islam, Md Rafiqul; Islam, Md Rafiqul; Alam, Muhammad Rashedul; Sayeed, Md Abu; Alam, Md Jahangir (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Congenital hypothyroidism (CH) is the most common congenital endocrine disorder seen in the newborn (1 in 4,000 births). It causes irreversible mental & physical disability if remains undetected. Diagnosis and treatment of CH before 3 months are mandatory to avoid CH. Objectives: The study was aimed to assess the level of knowledge regarding congenital hypothyroidism among the doctors in selected hospital in Dhaka city. Methods: A descriptive cross-sectional study was conducted and data was collected by using self-administered questionnaire. Data was analyzed using SPSS. Results: The mean age of the respondents was 40.5 years. Close to three-fifth (59.5%) of the respondents were in the age group 30-40 years. Above seventieth (71%) of the respondents were males and the rest were females.71% of the respondents knew that Infants born with congenital hypothyroidism may show no effects, or may display mild effects that often go unrecognized as a problem. The findings of this study revealed that more than half of the respondents have attended a training related to congenital hypothyroidism. It also reveals that more than half of the respondents had average knowledge regarding sign and symptoms of congenital hypothyroidism. Conclusion: In this study it has been reported that age of the respondents was associated with knowledge on sign and symptoms of congenital hypothyroidism. DS (Child) H J 2019; 35(1) : 27-32